Return to education by ethnicity: A case of Malaysia - Mohd Arshad, Mohd Nahar (http://econ.upm.edu.my/ijem/, 2016)
This study investigates the factors that influence earning differentials across three different ethnics in Malaysia—Bumiputra, Chinese and Indian. A specific focus is given to the effects of education on earnings. The variable is considered vital in restructuring the socioeconomic positions of these Malaysian ethnics. Mincerian earning functions have been estimated. Positive effects of education with varying magnitudes on earnings across the three ethnics have been found. Estimates on returns to education also vary across educational levels and gender for all the ethnics. The marginal rate of returns to university degree is the highest, as compared to other lower qualifications. A comparison across ethnicity shows that for those with university degrees, the returns for Indian ethnic were the highest at 24.85%, followed by Bumiputra at 22.55% and Chinese at 14.8%. There is also significant evidence of earning differentials attributable to occupational activities and regional/urban-rural locations in Malaysia.